High‐fat and high‐cholesterol diet rapidly induces non‐alcoholic steatohepatitis with advanced fibrosis in Sprague–Dawley rats. Issue 4 (9th June 2014) - Ichimura, Mayuko; Kawase, Miku; Masuzumi, Miki; Sakaki, Mika; Nagata, Yasuo; Tanaka, Kazunari; Suruga, Kazuhito; Tamaru, Shizuka; Kato, Shigeko; Tsuneyama, Koichi; Omagari, Katsuhisa
<x xml:space="preserve">Abstract</x> Aim The development of fibrosis is considered an important phase in the progress of non‐alcoholic steatohepatitis (NASH) towards the end stage of liver disease, including cirrhosis. However, few small animal models can display NASH‐associated fibrosis. We aimed to establish a dietary model of NASH with rapid progression to fibrosis using genetically normal rats. Methods Nine‐week‐old male Sprague–Dawley rats were fed with normal, high‐fat (HF), or two types of high‐fat and high‐cholesterol (HFC) diets for 9 weeks (n = 5 each). All HFC diets contained 1.25% or 2.5% cholesterol. Results The rats fed with the HF diet developed mild steatosis and inflammation without fibrosis at 18 weeks of age, whereas all rats given the HFC diet developed obvious steatosis and inflammation with hepatocyte ballooning and fibrosis. Two of five (40%) rats given the HFC diet containing 2.5% cholesterol progressed to liver cirrhosis. Hepatic total cholesterol levels were significantly higher in rats given the HFC, than the normal or HF diets. The HFC diet significantly and dose‐dependently decreased microsomal triglyceride transfer protein expression. Cholesterol tended to suppress carnitine palmitoyltransferase activity and adenosine triphosphate‐binding cassette transporter G5 expression. Adding cholesterol to the HF diet modified hepatic lipid metabolism at the molecular level. Conclusion The HFC diet induced hepatic features of NASH and eventually progressed cirrhosis in Sprague–Dawley rats within 9 weeks.